Social criteria for the location of a landfill (case, Metropolitan area of Bucaramanga) - Arias Rey, José Luis; Buitrago Rey, Javier Augusto (DIXI, 2013)
This paper intends to outline the social criteria to be taken into account for the selection of the emplacement for the new site of final disposal of solid waste in the metropolitan area of Bucaramanga. We begin with a characterization of the existing reality, which entails the urgent need to carry out the proper selection of a new site for the location of the landfill, hand in hand with the community, in order to improve on the work currently undertaken by diverse actors engaged in such activity.